MicroRNAs in a hypertrophic heart: from foetal life to adulthood. (1st June 2016) - Sadiq, Shahzad; Crowley, Tamsyn M.; Charchar, Fadi J.; Sanigorski, Andrew; Lewandowski, Paul A.
ABSTRACT: The heart is the first organ to form and undergoes adaptive remodelling with age. Ventricular hypertrophy is one such adaptation, which allows the heart to cope with an increase in cardiac demand. This adaptation is necessary as part of natural growth from foetal life to adulthood. It may also occur in response to resistance in blood flow due to various insults on the heart and vessels that accumulate with age. The heart can only compensate to this increase in workload to a certain extent without losing its functional architecture, ultimately resulting in heart failure. Many genes have been implicated in cardiac hypertrophy, however none have been shown conclusively to be responsible for pathological cardiac hypertrophy. MicroRNAs offer an alternative mechanism for cellular regulation by altering gene expression. Since 1993 when the function of a non‐coding DNA sequence was first discovered in the model organism Caenorhabditis elegans, many microRNAs have been implicated in having a central role in numerous physiological and pathological cellular processes. The level of control these antisense oligonucleotides offer can often be exploited to manipulate the expression of target genes. Moreover, altered levels of microRNAs can serve as diagnostic biomarkers, with the prospect of diagnosing a disease process as early as during foetal life. Therefore, it is vital to ascertain and investigate the function of microRNAs that are involved in heart development and subsequent ventricular remodelling. Here we present an overview of the complicated network of microRNAs and their target genes that have previously been implicated in cardiogenesis and hypertrophy. It is interesting to note that microRNAs in both of these growth processes can be of possible remedial value to counter a similar disease pathophysiology.